The Study of Defects on Galvanically Plated Polymeric Parts - Andrsova, Zuzana; Podzimek, Petr; Kejzlar, Pavel (Manufacturing Technology Journal, 2016)
Galvanic plating of polymeric structural parts is widely used in many industrial branches, e.g. in automotive. Minor errors in their manufacturing process are responsible for presence of surface defects. These defects, especially in the case of visual and decorative parts, are unacceptable. This paper demonstrates the usage of optical and electron microscopy to reveal and solve common problems in industrial production. Different types of galvanic plating defects on injection molded parts made of ABS, PC/ABS and PA manifest themselves by different ways.
Keywords: Microscopy; Coating; Analysis; Defect; Polymer